Unveiling of phosphodiesterase-5 hot residues binding to xanthine derivatives for erectile dysfunction therapy: A computational drug repurposing approach - Elzupir, Amin O.; Almahmoud, Sondos A. J. (PLOS ONE, 2025)
Overexpression of phosphodiesterase 5 (PDE-5) presents a compelling target for the therapy of erectile dysfunction. Sildenafil and other conventional PDE-5 inhibitors may lead to adverse effects, including visual disturbances and migraines. Therefore, the investigation of novel inhibitors with enhanced safety profiles is imperative. This research employed a computational drug repurposing approach to assess US-FDA-approved xanthine derivatives (XDs) for their efficacy in targeting PDE-5. XDs exhibit a favorable affinity for the active site of the PDE-5 receptor, with binding scores between −10.0 kcal/mol and −6.3 kcal/mol for linagliptin and theobromine, respectively. The top-ranked docked Xds then underwent 300-nanosecond molecular dynamics simulations. Linagliptin demonstrated greater stability in the binding pocket (RMSD = 1.60 ± 0.34) compared to the typical inhibitor sildenafil (RMSD = 1.70 ± 0.27). The findings were corroborated by MM-PBSA calculation, which showed that linagliptin’s binding free energy of −45.6 ± 4.3 kcal/mol comparable with sildenafil’s −49.0 ± 3.1 kcal/mol. This value is notably higher than that of the deprotonated form of sildenafil, which is present at a 37.06% ratio at physiological pH 7.4. Additionally, we used per-residue energy decomposition to identify crucial residues for PDE-5 activity and thoroughly investigated hydrogen bond occupancy. This study points outthe potential of linagliptin as a PDE-5 inhibitor, paving the way for the development of a safe treatment for erectile dysfunction.